Peran Lembaga Keuangan dalam Mendorong Usaha Kecil dan Menengah di Masa Pemulihan Pandemi Covid-19 (Studi Kasus Kawasan Wisata Religi Makam Gus-Dur) - Kisan Mafawiz; Peni Haryanti (Institut Agama Islam Negeri Palopo, 2022)
The COVID-19 pandemic has made UMKM activists at Gus Dur's grave experience very minimal income due to the lack of visitors. In November 2021, the religious tourism area of Gus Dur's tomb was reopened, and the situation of micro, small and medium enterprises there was not very normal, where traders needed capital to restart their businesses and save for urgent needs. Therefore, the purpose of this study is to determine the situation of micro, small and medium enterprises during the recovery period from the COVID-19 pandemic and the role of financial institutions. This study uses a qualitative method with a case study approach adapted from Robert K. Yin. The results of this study indicate that although the situation there is not normal and financial institutions function as fund collectors and fund distribution.